2014
DOI: 10.1158/1055-9965.epi-14-0172
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic Intake of Dairy Products and Dietary Calcium and Colorectal Cancer Survival—Results from the EPIC Cohort Study

Abstract: Background: We investigated whether prediagnostic reported intake of dairy products and dietary calcium is associated with colorectal cancer survival.Methods: Data from 3,859 subjects with colorectal cancer (42.1% male; mean age at diagnosis, 64.2 AE 8.1 years) in the European Investigation into Cancer and Nutrition cohort were analyzed. Intake of dairy products and dietary calcium was assessed at baseline (1992-2000) using validated, country-specific dietary questionnaires. Multivariable Cox regression models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 42 publications
7
34
0
Order By: Relevance
“…The study population may not be entirely representative of the wider UK population, since all recruited participants were born in the county of Hertfordshire, were still living there in their eighth decade and were all Caucasian and therefore do not reflect the diversity of other populations in the UK. However, we have previously demonstrated that this cohort is representative of the general population with regard to anthropometric body build and lifestyle factors, such as smoking, alcohol intake and dietary calcium intake, which was in line with data found in the European Investigation into Cancer and Nutrition (EPIC) cohort [48], therefore suggesting that selection bias was minimal [17]. In addition, a 'healthy' responder bias is evident within the HCS [17]; however, it is unlikely to have affected the observed associations between sleep quality and bone parameters.…”
Section: Discussionsupporting
confidence: 89%
“…The study population may not be entirely representative of the wider UK population, since all recruited participants were born in the county of Hertfordshire, were still living there in their eighth decade and were all Caucasian and therefore do not reflect the diversity of other populations in the UK. However, we have previously demonstrated that this cohort is representative of the general population with regard to anthropometric body build and lifestyle factors, such as smoking, alcohol intake and dietary calcium intake, which was in line with data found in the European Investigation into Cancer and Nutrition (EPIC) cohort [48], therefore suggesting that selection bias was minimal [17]. In addition, a 'healthy' responder bias is evident within the HCS [17]; however, it is unlikely to have affected the observed associations between sleep quality and bone parameters.…”
Section: Discussionsupporting
confidence: 89%
“…There is mixed evidence from prospective studies concerning a role of dairy food consumption in mortality risk (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Consistent with our results, in the Whitehall II Study (21), higher consumption of dairy products was associated with reduced all-cause mortality risk in comparison with the lowest intake.…”
Section: Discussionsupporting
confidence: 86%
“…Few epidemiologic studies have investigated whether a high dairy food intake is associated with cancer mortality risk (20,(27)(28)(29). While in the Michaëlsson et al study high milk intake was associated with higher cancer mortality risk in Swedish women but not men, there were no significant associations between cheese or yogurt and cancer mortality risk (20).…”
Section: Discussionmentioning
confidence: 98%
“…Information on vital status and movement of participants was obtained through record linkage with the municipal and national mortality registries most countries or through a combination of methods, including health insurance records, cancer and pathology registries, and active follow-up of study subjects and their next-of-kin [26]. The outcome of the study was mortality (all-cause or breast cancer-specific).…”
Section: Methodsmentioning
confidence: 99%